Acessando a comunidade de mesopredadores em uma região altamente fragmentada de mata atlântica a partir do eDNA e iDNA - Pereira, Anderson Coimbra (Universidade Federal de São Carlos, 2024)
The Atlantic Forest is one of the most biodiverse yet threatened biomes globally, with significant loss of its original area due to fragmentation and human expansion. The Pernambuco Endemism Center (CEP), located north of the São Francisco River mouth, is among the most devastated regions of this biome, hosting endemic species and high phylogenetic diversity, although its remaining areas are increasingly isolated and degraded. The fragmentation of CEP poses a serious threat to the survival of various species and undermines the ecological functioning of the biome, marking it as a priority area for conservation studies. Currently, large mammals are absent from the CEP due to intense anthropogenic pressure, and remaining predators are mesopredators, surviving in low densities and playing crucial ecological roles. This study focuses on the conservation of these mesopredators by detecting their presence to enhance knowledge of their distributions and identify priority areas for conservation. Innovative monitoring approaches are essential for understanding the presence of threatened species and guiding preservation actions. The objectives included identifying mesopredator presence in CEP forest fragments and pinpointing areas of conservation priorities for those species. Monitoring employed environmental DNA (eDNA) and invertebrate-derived DNA (iDNA) techniques, analyzing water samples and stomach contents of flies and mosquitoes, respectively. Additionally, species distribution modeling (SDM) was conducted to identify areas with conservation potential for six mesopredator species recorded in the region: Leopardus pardalis, Didelphis aurita, Didelphis albiventris, Procyon cancrivorus, Nasua nasua, and Cerdocyon thous. Collections were made from 13 forest fragments in CEP, utilizing metabarcoding analyses with 12SrRNA and 16SrRNA markers to detect mesopredator species presence. Results demonstrated the effectiveness of eDNA and iDNA methodologies for monitoring low-abundance species in fragmented areas, identifying C. thous and D. albiventris in five of the analyzed fragments; the iDNA from flies and the 16S marker were more effective for target species identification. The SDM incorporated environmental, land cover, anthropogenic, and topographical variables to predict favorable occurrence areas for these species' conservation. The modeling outcomes forecast potential species distributions in response to the analyzed variables, identifying viable forest fragments for population protection. This study provides critical insights for conserving mesopredators and the overall faunal community in CEP. By identifying occurrence areas and potential habitats, the research aids in developing conservation strategies that can benefit local biodiversity. Thus, the present study not only advances knowledge about mesopredators but also reinforces the importance of integrated actions to protect the threatened fauna of the Centro de Endemismo Pernambuco.
Assessing the mesopredator community in a highly fragmented region of the Atlantic Forest using eDNA and iDNA
Keywords: Fragmentação de habitat; Mata Atlântica; Genética da conservação; Modelagem de distribuição de espécies; Habitat fragmentation; Atlantic Forest; Conservation genetics; Species distribution modeling; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS